El papel de las instituciones en la economía de mercado (2016)
The political dynamic established and set challenges for the economy in the world in many moments of history, as the late twentieth century and begin the twenty-first century, not only by changes in the way to manage the states, but the transitions they coincided with the rise of liberal orthodoxy. Questioning again, market efficiency to solve problems of equity and welfare, as well as the difficulty of achieving a global environment with less risk and greater certainty. In this context, they agreed on the urgent need to reconsider a new path of development based on the revaluation of social democracy and the pursuit of its compatibility with the market, demanding to reconsider the role of citizens, the state and government in the scene of a democratic renewal, which is essential to an institutional architecture that facilitates the formality and some institutional arrangements to track and appropriate adjustments for balanced, effective and efficient operation capable of responding to the complex problems of societies from the participation until the responsibility for decisions and their impacts and consequences.